(untitled) (Global Journal of Sciences, 2025)
Certainly, fractional calculus has grabbed the keen interest of numerous investigators in the last couple of decades. Numerous real-world problems and demonstrations have involved the development of the Caputo-Fabrizio fractional operator. Our article’s primary goal is to enhance Hermite-Hadamard (H-H) integral inequality and its generalizations by applying the Caputo-Fabrizio fractional integral operator (CFFIO) and the preinvexity concept. We additionally offer some applications of our key findings to specific methods.